Cohabitation an gender disparities in labor supply in Brazil - Stehmann, Júlia Alves (2025)
This paper explores the relationship between cohabitation and labor supply, specifically focusing on how this connection influences womens decision-making and outcomes in the workforce. To assess the impact of cohabitation on labor supply, we estimated Goussé, Jacquemet, and Robin\'s (2017) model of the marriage market and labor supply using data from the Continuous Brazilian National Household Survey (PNADC) for the period 2013-2019. Although the PNADC does not directly inquire about individuals marital status, we sedinformation regarding their roles within the household to construct a proxy for cohabitation. Based on the model estimation, we simulate the effects on womens time allocation (both single and married) of (i) eliminating the gender wage gap, (ii) equalizing preference parameters between men and women, and (iii) removing womens comparative advantage in home production. Our findings reveal a significant trend of positive assortative mating, indicating a preference for partners with similar traits who adhere to traditional gender roles and avoid deviations from these social norms. Furthermore, we observe that womens lower labor supply is primarily driven by domestic responsibilities, personal preferences, and the market wage structure. In contrast, the allocation of time to non-market activities is largely explained by womens comparative advantage in home production.